2004
DOI: 10.1002/ajmg.a.30269
|View full text |Cite
|
Sign up to set email alerts
|

Three patients with 9p deletions including DMRT1 and DMRT2: A girl with XY complement, bilateral ovotestes, and extreme growth retardation, and two XX females with normal pubertal development

Abstract: It is well documented that distal 9p monosomy can be associated with XY sex reversal. Recently, the possibility of DMRT1 and/or DMRT2 (the genes for doublesex and mab-3 related transcription factor 1 and 2) being the sex determining genes(s) at 9p has been raised. DMRT1 and DMRT2 map near the 9p telomere, distal of marker D9S1779. We describe here three unrelated females with distal 9p monosomy, one with XY complement and two with XX complements. In each individual, fluorescent in situ hybridization predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 29 publications
(56 reference statements)
1
37
0
Order By: Relevance
“…It is not clear why one deletion (present case) is associated with ovotesticular DSD and the other deletion with XY gonadal dysgenesis. The size of the deletion does not explain the different phenotypes as Õ unap et al (23) reported on a patient with bilateral ovotestes and an unbalanced translocation 46,XY,der(9)t(7;9)(q32;p24) leading to a deletion of DMRT1/DMRT2.…”
Section: Discussionmentioning
confidence: 94%
“…It is not clear why one deletion (present case) is associated with ovotesticular DSD and the other deletion with XY gonadal dysgenesis. The size of the deletion does not explain the different phenotypes as Õ unap et al (23) reported on a patient with bilateral ovotestes and an unbalanced translocation 46,XY,der(9)t(7;9)(q32;p24) leading to a deletion of DMRT1/DMRT2.…”
Section: Discussionmentioning
confidence: 94%
“…Second, DMRT1 was expressed exclusively in testes among 50 investigated human tissues. Further evidence for DMRT1 as a male sexual regulator came either from the later studies of its expression in human embryos (Moniot et al, 2000) or from additional reports describing sex-reversed patients with the monosomy of 9p (Raymond et al, 1999a;Muroya et al, 2000;Õunap et al, 2004;Privitera et al, 2005;Vinci et al, 2007). In the meantime, the group of Zarkower from the University of Minnesota (Raymond et al, 1999b) and the group of Sinclair from the University of Melbourne (Smith et al, 1999a) published very important data about DMRT1 expression during mouse, chicken and alligator embryogenesis.…”
Section: Dmrt -Vertebrate Dm Domain Gene Familymentioning
confidence: 99%
“…1D). The deletion of human DM genes on chromosome 9p is associated with intersexual development (6,27,31,49,55,59,63). Although originally described in relation to sex-determining pathways (67), an extended family of DM genes is proposed to function in general aspects of developmental patterning in vertebrates (35).…”
mentioning
confidence: 99%